The reason why the rossios should be reinvented in the contemporary city - Freire, Maria (2013)
This approach brings up the urban multifunctionality of open urban spaces and reflects on the importance of the ethical issues, concerning the Nature and Culture. It starts with the definition of rossio, an open urban space Portuguese typology, discussing its functions, location and form; move towards the importance of rossio in the context of the historic and contemporary city; and ends with the explanation of its potential for today’s society. The aim is to value this singular open space, to argue for its adaptive capacity in the improvement of our cities, and to underline its character as a fundamental urban unit.